Private Data Release via Learning Thresholds - Hardt, Moritz; Rothblum, Guy; Servedio, Rocco A. (CoRR, SODA, 2011)
This work considers computationally efficient privacy preserving data release. We study the task of analyzing a database containing sensitive information about individual participants. Given a set of statistical queries on the data, we want to release approximate answers to the queries while also guaranteeing differential privacy— protecting each participant’s sensitive data. Our focus is on computationally efficient data release algorithms; we seek algorithms whose running time is polynomial, or at least sub-exponential, in the data dimensionality. Our primary contribution is a computationally efficient reduction from differentially private data release for a class of counting queries, to learning thresholded sums of predicates from a related class.